USE OF ETHNOVETERINARY REMEDIES IN THE MANAGEMENT OF FOOT AND MOUTH DISEASE LESIONS IN A DIARY HERD - Gakuya, D. W.; Mulei, C. M.; Wekesa, S. B. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
An outbreak of Foot and Mouth Disease (FMD) affecting 95 (57.2%) out of 166 cattle occurred in a medium-scale dairy farm in Kikuyu district, Kenya. Ethnoveterinary remedies of natural Soda ash solution (97% sodium bicarbonate), honey and finger millet flour were used to manage the FMD lesions. The lesions were washed with soda ash solution to remove the necrotic tissue after which raw honey and finger millet flour were applied to the cleaned lesions. The lesions were examined daily and those with necrotic material washed again with the Soda ash solution. Honey and finger millet flour were applied daily for three days. There was rapid healing of the lesions with the animals resuming feeding after three days. The fast healing of the lesions vindicates the use of these cheap, locally available and easy to apply products in the management of FMD lesions. However, more studies are needed to evaluate further their potencies.